The general formula: y=mx+b
(6,2) ⇒ x=6,y=2
m=3
b=?
2=3*6+b
2=18+b
b=-16
<u>y=3m-16</u>
First we can simplify f(x) to make it a little easier. We can write it as
4x^3+2x^2-7x+4 by combining like terms
The we just subtract g(x) from f(x) and simplify
4x^3+2x^2-7x+4-(5x^3-7x+4) and remember to distribute the negative to g(x)
4x^3+2x^2-7x+4-5x^3+7x-4 (combine like terms)
-x^3+2x^2
In factored form, this becomes
-x^2(x-2)
Hope this helps
5(n + 3) + 4n
5n + 15 + 4n Distributive property
5n + 4n = 9n Combine like terms
9n + 15 Final answer
Answer: 9n + 15